Toward the Impact of Job Satisfaction and Collective Efficacy on EFL Teachers’ Professional Commitment - Zhang, Fan (Frontiers in Psychology, 2022)
Since the success of any educational system is tied to the teachers’ professional commitment, discovering the determinants of this construct seems vital. In line with this, a huge number of inquiries have evaluated the effects of personal, contextual, and professional variables on teachers’ professional commitment. However, the impacts of job satisfaction and collective efficacy have remained unclear. Against this backdrop, the current review article seeks to theoretically explain the impacts of these constructs on EFL teachers’ professional commitment using the available documents. The review findings illuminated that EFL teachers’ professional commitment heavily relies on their job satisfaction and collective efficacy beliefs. The implications for educational principals and teacher educators are finally discussed.